2013
DOI: 10.1111/apa.12334
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-integrated electroencephalography in male newborns <30 weeks’ of gestation and unfavourable neurodevelopmental outcome at three years is less mature when compared to females

Abstract: Being male with an abnormal outcome at 3 years of age is reflected by a less mature early aEEG when compared with the one of females. This association is independent of IVH and medication and was less evident with increasing gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Several studies indicate that the amplitude of the lower margin is associated with GA and postnatal age, and that the lower margin increases as GA increases. 10 , 23 , 24 , 25 , 26 With regard to sex, Olishar et al 27 found that male sex and a lower GA increased the likelihood of abnormalities in the aEEG composite score, defined by the baseline tracing, sleep–wake cycle, and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that the amplitude of the lower margin is associated with GA and postnatal age, and that the lower margin increases as GA increases. 10 , 23 , 24 , 25 , 26 With regard to sex, Olishar et al 27 found that male sex and a lower GA increased the likelihood of abnormalities in the aEEG composite score, defined by the baseline tracing, sleep–wake cycle, and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding aEEG, which is an established method of newborn brain monitoring and evaluation of brain maturation, many studies have been published, but until now, none of them have specifically investigated differences in aEEG signals between male and female infants [6,12,13]. Recently Olischar et al [18] showed that male preterm infants born below 30 weeks gestational age with an impaired neurodevelopmental outcome at the age of 3 years, show more burst suppression background patterns and less cycling than female preterm infants. They did not show a difference in aEEG signals between male and female preterm infants with normal neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…39 Centers are increasingly publishing studies supporting the neurologic prognostic value of aEEG and conventional EEG studies for infants born very premature. 39,[53][54][55][56][57] Abnormal electrographic studies have predictive power for both motor and cognitive impairments in this population, 53,57 even as early as the first 12 to 24 h of life. 56 Additionally, aberrant electrocortical background activity has prognostic implications for neurodevelopmental outcome that exceeds the predictive abilities of HUS.…”
Section: Introductionmentioning
confidence: 96%